2022
DOI: 10.1007/s13399-022-03387-z
|View full text |Cite
|
Sign up to set email alerts
|

Composting date palm residues promotes circular agriculture in oases

Abstract: Dry leaves of date palms (DPs) are by-products of date cultivation that are often mismanaged in oasis agroecosystems. Ideally, they should be upcycled in a circular agriculture model before producing and exporting high-value products. Compost inputs enhance soil organic matter and conserve soil. This study investigated composting of four mixtures based on farming system requirements and the availability of organic resources. The DPs were used alone or combined with sheep manure and rock phosphate. We experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 57 publications
0
12
0
2
Order By: Relevance
“…D'après Dhehibi (2020), l'accumulation des sous-produits génère des effets néfastes tels que la prolifération des insectes et des parasites. Selon Chakroune et al (2005), la décomposition des résidus de culture constitue une cause de dissémination du bayoud ; leur gestion incontrôlée peut provoquer des incendies dans les oasis (Hakkou et Bouakka, 2004 ;El Janati et al, 2022). De plus, Bensidhom et al (2018) affirment que le gaz issus des déchets du palmier dattier contient une quantité importante de CH 4 et de H 2 , ce qui leur confère de bonnes propriétés de combustion.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…D'après Dhehibi (2020), l'accumulation des sous-produits génère des effets néfastes tels que la prolifération des insectes et des parasites. Selon Chakroune et al (2005), la décomposition des résidus de culture constitue une cause de dissémination du bayoud ; leur gestion incontrôlée peut provoquer des incendies dans les oasis (Hakkou et Bouakka, 2004 ;El Janati et al, 2022). De plus, Bensidhom et al (2018) affirment que le gaz issus des déchets du palmier dattier contient une quantité importante de CH 4 et de H 2 , ce qui leur confère de bonnes propriétés de combustion.…”
Section: Discussionunclassified
“…albedinis (bayoud), l'accumulation et la décomposition des déchets contaminés sont une cause d'extension des foyers de la maladie et de propagation de champignons pathogènes (Hakkou et Bouakka, 2004 ;Chakroune et al, 2005). Selon El Janati et al (2022), les sous-produits du palmier dattier abandonnés dans les champs peuvent causer une infestation d'insectes et de maladies, ou servir de combustible pour des incendies accidentels. L'utilisation des résidus a diminué parallèlement à l'augmentation de la culture du palmier dattier (Tahir et al, 2020).…”
Section: Introductionunclassified
“…Recycling these organic waste products is a potential solution to provide organic inputs and address the current manure shortage. El Janati et al (2023) [22] observed that utilizing date palm compost produced on farms could effectively address the lack of organic inputs and enhance the organic date production chain. In the deserts of the Arabian Peninsula and North Africa, oasian agroecosystems have long been the only viable crop production system.…”
Section: Challenges For Maintaining Sustainable Agriculture In Arid A...mentioning
confidence: 99%
“…According to El-Janati et al (2023) [22], approximately 120 million date palm trees exist in the world. The date palm is more suitable for cultivation in arid and semi-arid regions of the globe [20] due to its resilience and adaptability to harsh environmental conditions, including drought, salinity, high temperature, and poor soil conditions.…”
Section: Geographic Distribution Of the Cultivated Date Palmmentioning
confidence: 99%
“…El Janati et al [18] reported that 1 ha of palm grove produces around 2.4 t of dried date palm residues per year. This renewable resource is poorly recovered and mostly abandoned in fields, which can cause insect and disease infestation, or other environmental issues like accidental fires [19]. In recent studies, date palm residues co-composted with sheep manure showed promise for increasing the soil fertility and corn yields in an arid agroecosystem [20].…”
Section: Introductionmentioning
confidence: 99%